2015
DOI: 10.1016/j.ajem.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for intravenous vasodilators in ED patients with acute heart failure: a systematic review

Abstract: There are nearly 700,000 annual US emergency department (ED) visits for acute heart failure (AHF). While blood pressure is elevated on most of these visits, acute therapy remains focused on preload and not afterload reduction. Data from recent prospective studies suggest AHF patients with concomitant acute hypertension benefit from intravenous (IV) vasodilators. To better understand the use of vasodilators for such patients, we conducted a systematic review of 1) currently available intravenous vasodilators fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…The landmark Antihypertensive and Lipid‐Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) study included 404 patients with HFpEF and showed reduced rates of HFpEF in patients on chlorthalidone and a reduced risk for HF hospitalization . Although there are several studies demonstrating improvement in symptoms with blood‐pressure reduction in acute HF patients with HTN, the impact of blood‐pressure control in the acute setting on clinical outcomes and in the HFpEF population in particular has not been well studied …”
Section: Discussionmentioning
confidence: 99%
“…The landmark Antihypertensive and Lipid‐Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) study included 404 patients with HFpEF and showed reduced rates of HFpEF in patients on chlorthalidone and a reduced risk for HF hospitalization . Although there are several studies demonstrating improvement in symptoms with blood‐pressure reduction in acute HF patients with HTN, the impact of blood‐pressure control in the acute setting on clinical outcomes and in the HFpEF population in particular has not been well studied …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clinical evidence has also revealed the therapeutic role of vasodilators in hypertensive patients with AHF 919. However, these results generally come from observational studies, and evidence-based therapy in AHF is lacking 420. Indeed, although previous pilot trials, mostly from case reports or case series,1421 have suggested intravenous urapidil as a potential therapeutic option in patients with hypertension and AHF, randomized controlled trials are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is increasing evidence that the prevalence of AHF is substantial in older adult patients complicated with hypertension, although evidence-based treatment strategies are generally lacking 4. The development of novel pharmacologic agents for patients with both hypertension and AHF is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies reported an absence of benefit in patients treated with nitrates [23,24], whereas others reported a significant improvement in terms of mortality and severe outcome after nitrate utilization [16,25]. A systematic review concluded that prescription of nitrates is based more on a clinical dogma than on high-quality trials, and reliable data on survival benefit are lacking [26]. Despite the absence of many high-quality, generalizable, randomized trials, evidence of benefit of a treatment strategy including nitrates in AHF has still been reported (in the ALARM-HF study), with the use of a powerful statistical tool to match patients [25].…”
Section: Discussionmentioning
confidence: 94%